Analisis Kelayakan Buku Ajar Kurikulum 2013 Pada Mata Pelajaran IPS Kelas VII SMP Nurmairina (LITERATUS, 2022)
This study aims to find out how the feasibility of the 2013 curriculum textbooks on social studies class VII SMP. This research uses descriptive research. The research aims to systematically describe or explain the facts from the 2013 curriculum book by using interviews with experts, namely language experts and graphic experts to assess the feasibility of textbooks. Based on the research that has been done it is known that (1). Language or grammar and sentences in the student book are partly in accordance with linguistic rules. However, there are still many who are not in accordance with the appropriate language rules for class VII junior high school students. (2). Graphical aspects presented in textbooks for class VII students in social studies lessons are not in accordance with the education unit level. Books can be classified into three sections, namely elementary level users for students aged 6-10 years, intermediate students aged 10-14 years, and Advanced for students aged 14 years and over. As for Class VII students in the Intermediate category aged 10-14 years. Graphic aspects must be made interesting with illustrations that are also interesting but simple.